Peran Pelatihan dengan Mediasi Kesesuaian Pekerjaan, Pembelajaran, dan Keterlibatan Kerja Terhadap Kinerja Pegawai Pemerintah Kota Madiun - Farida, Nur Farida; Hendarsjah, Hidajat (School of Business, Bogor Agricultural University (SB-IPB), 2022)
In this study we investigate how training affects job performance. We propose the multiple mediator model as a mediating mechanism that transmits the positive effects of training on job performance. The aim of this study was to examine the degree of direct and indirect relationship between training and job performance, as well as to understand the mediating role of person job fit, learning from training and work engagement. The hypothesis was tested on a sample of 225 government officer using a regression test using Baron Kenny's Causal Step method. The results showed a direct relationship between training and performance. The results of the study found that person job fit and work engagement partially mediate the relationship between training and performance. The findings of this study provide useful information for policy makers to improve job fit and work engagement and performance through training. Keywords: training, job performance, person job fit, learning from training, work engagement